Prenatal exposure to the organophosphate insecticide chlorpyrifos enhances brain oxidative stress and prostaglandin E2 synthesis in a mouse model of idiopathic autism. Issue 1 (December 2016) - De Felice, Alessia; Greco, Anita; Calamandrei, Gemma; Minghetti, Luisa
Abstract Background Autism spectrum disorders (ASD) are emerging as polygenic and multifactorial disorders in which complex interactions between defective genes and early exposure to environmental stressors impact on the correct neurodevelopment and brain processes. Organophosphate insecticides, among which chlorpyrifos (CPF), are widely diffused environmental toxicants associated with neurobehavioral deficits and increased risk of ASD occurrence in children. Oxidative stress and dysregulated immune responses are implicated in both organophosphate neurodevelopmental effects and ASD etiopathogenesis. BTBR T+tf/J mice, a well-studied model of idiopathic autism, show several behavioral and immunological alterations found in ASD children, and we recently showed that CPF gestational exposure strengthened some of these autistic-like traits. In the present study, we aimed at investigating whether the behavioral effects of gestational CPF administration are associated with brain increased oxidative stress and altered lipid mediator profile. Methods Brain levels of F2 -isoprostanes (15-F2t -IsoP), as index of in vivo oxidative stress, and prostaglandin E2 (PGE2 ), a major arachidonic acid metabolite released by immune cells and by specific glutamatergic neuron populations mainly in cortex and hippocampus, were assessed by specific enzyme-immuno assays in brain homogenates from BTBR T+tf/J and C57Bl6/J mice, exposed during gestation to either vehicle or CPF. Measures were performed in mice of both sexes, at different postnatal stages (PNDs 1, 21, and 70). Results At birth, BTBR T+tf/J mice exhibited higher baseline 15-F2t -IsoP levels as compared to C57Bl6/J mice, suggestive of greater oxidative stress processes. Gestational treatment with CPF-enhanced 15-F2t -IsoP and PGE2 levels in strain- and age-dependent manner, with 15-F2t -IsoP increased in BTBR T+tf/J mice at PNDs 1 and 21, and PGE2 elevated in BTBR T+tf/J mice at PNDs 21 and 70. At PND 21, CPF effects were sex-dependent being the increase of the two metabolites mainly associated with male mice. CPF treatment also induced a reduction of somatic growth, which reached statistical significance at PND 21. Conclusions These findings indicate that the autistic-like BTBR T+tf/J strain is highly vulnerable to environmental stressors during gestational period. The results further support the hypothesis that oxidative stress might be the link between environmental neurotoxicants such as CPF and ASD. The increased levels of oxidative stress during early postnatal life could result in delayed and long-lasting alterations in specific pathways relevant to ASD, of which PGE2 signaling represents an important one.